Finance-dominated capitalism and redistribution of income: A Kaleckian perspective - Eckhard Hein (Levy Economics Institute of Bard College, 2013)
This paper examines a major channel through which financialization or finance-dominated capitalism affects macroeconomic performance: the distribution channel. Empirical data for the following dimensions of redistribution in the period of finance-dominated capitalism since the early 1980s is provided for 15 advanced capitalist economies: functional distribution, personal/household distribution, and the share and composition of top incomes. Based on the Kaleckian approach to the determination of income shares, the effects of financialization on functional income distribution are studied in more detail. Some stylized facts of financialization are integrated into the Kaleckian approach, and by means of reviewing empirical and econometric literature it is found that financialization and neoliberalism have contributed to the falling labor income share since the early 1980s through three main Kaleckian channels: (1) a shift in the sectoral composition of the economy; (2) an increase in management salaries and rising profit claims of the rentiers, and thus in overheads; and (3) weakened trade union bargaining power.
Keywords: D31; D33; D43; 330; finance-dominated capitalism; distribution of income; Kaleckian price and distribution theory